Intrinsic risk factors for acute ankle injuries among male soccer players: a prospective cohort study - Engebretsen, A. H.; Myklebust, G.; Holme, I.; Engebretsen, L.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2010)
This prospective cohort study was conducted to identify risk factors for acute ankle injuries among male soccer players. A total of 508 players representing 31 amateur teams were tested during the 2004 pre-season through a questionnaire on previous injury and function score (foot and ankle outcome score; FAOS), functional tests (balance tests on the floor and a balance mat) and a clinical examination of the ankle. Generalized estimating equations were used in univariate analyses to identify candidate risk factors, and factors with a P-value <0.10 were then examined in a multivariate model. During the season, 56 acute ankle injuries, affecting 46 legs (43 players), were registered. Univariate analyses identified a history of previous acute ankle injuries [odds ratio (OR) per previous injury: 1.25, 95% confidence interval (CI) 1.09-1.43] and the FAOS sub-score "Pain" (OR for a 10-point difference in score: 0.81, 95% CI 0.62-1.04) as candidate risk factors. In a multivariate analysis, only the number of previous acute ankle injuries proved to be a significant (adjusted OR per previous injury: 1.23; 95% CI 1.06-1.41, P=0.005) predictor of new injuries. Function scores, functional tests and clinical examination could not independently identify players at an increased risk in this study.